Simulation system for improving tennis stroke motion - Okamura, A.; Ishi, T.; Mitsuhashi, D. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to construct a system that can simulate tennis stroke motion for competition level enhancement of players. To do so, 10 female tennis club players (1 9- 23 years old) of University of Tsukuba were selected for a biomechanics study using three-dimensional stroke motion analysis method, in a total of 10 trials. Using obtained results on joint angles of the whole body, the best results of university tournament and racket head speed at impact, a database was constructed. Principal component analysis was used to classify the motion patterns into the principal component scores. Based on the principal component score and optimization theory, we generated a simulation system to predict competition level and racket head speed, and thus a new stroke motion, which can be expressed using 30 animations.